Robust Heterostructures in Two‐Dimensional Perovskites by Threshold‐Dominating Anion Exchange. Issue 31 (7th July 2022) - He, Chengyu; Li, Jing; Bao, Yanan; Li, Jianliang; Wang, Hengshan; Zhang, Mingqun; Li, HuaFeng; Tang, Huayi; Sun, Zhiguang; Zhang, Qi; Fang, Yurui; Xu, Jiao; et al.
Abstract: Heterostructures play an irreplaceable role in high‐performance optoelectronic devices. However, the preparation of robust perovskite heterostructures is challenging due to spontaneous interdiffusion of halogen anions. Herein, a vapor‐phase anion exchange method universally suitable for the preparation of robust 2D Ruddlesden–Popper perovskite (RPP) heterostructures is developed. A variety of heterostructures are fabricated based on exfoliated RPP microplates (MPs). Depending on the specific organic cations, the heterostructures can be either sharp and uniform, or broad and gradient, suggesting a new anion diffusion behavior different from that in 3D perovskites. Further experimental studies reveal that the lateral transport of anions follows a threshold‐dominating mechanism, while the vertical transport can be partially or completely suppressed by organic cations. Subsequently, quantitative investigation of anion diffusion in 2D perovskites is conducted. The lateral diffusion coefficient of halogen anions is calculated to be 6 to 7 orders of magnitude larger than the vertical coefficient, consistent with the observed highly anisotropic anion diffusion. In addition, it is shown that the anion exchange threshold can also enhance the thermodynamic stability of the heterostructures at elevated temperature. These results provide a general method to fabricate robust lateral RPP heterostructures, and offer important insights into anion behavior in low‐dimensional perovskites. Abstract : A vapor‐phase anion exchange method universally suitable for fabricating various robust 2D Ruddlesden–Popper perovskite (RPP) heterostructures is developed. The large organic cation spacers confine the anion diffusion in the 2D Pb‐X network, leading to sharp and robust heterostructures. A threshold‐dominating diffusion mechanism is proposed and experimentally verified in these 2D microplates.